カイヒョウ ジョウ セキセツ オヨビ ヒセツ ニ フクマレル カイエン - 長田, 和雄; オサダ, カズオ; 西尾, 文彦; ニシオ, フミヒコ; 樋口, 敬二; ヒグチ, ケイジ; Osada, Kazuo; Nishio, Fumihiko; Higuchi, Keiji (1988)
P(論文) 昭和基地周辺での海氷の状態と海塩輸送の関係を知る目的で, 降雪, 飛雪および海氷上の積雪を採取した。得た試料の融水の電気伝導度の測定結果から, 海塩の輸送機構を推論した。試料の電気伝導度は, 降雪で2.5-18μS/cm, ブリザード時の飛雪および海氷上の積雪で20-(10)^3μS/cm(一部は(10)^4μS/cm以上)で(10)^2μS/cm程度の場合が多かった。海氷上の積雪の存在状況と電気伝導度の関係は, 海氷の露出した地域の存在により, 海氷上の積雪の電気伝導度が高い値を示した。ブリザード時には, 降雪に起因する飛雪と, 塩分の高い積雪層の削剥に起因する飛雪とが混在して輸送されると考えられる。また, 塩分の高い積雪層の削剥起因する飛雪の水分を蒸発させる諸条件が整えば, 海塩粒子の生成する可能性を示した。 Fallen snow, snow drift and deposited snow on sea ice were collected in 1986 near Syowa Station, East Antarctica. Electroconductivity measurments of meltwater of the collected samples were performed at Syowa Station. The electroconductivities of the samples were mostly of order (10)^2μS/cm as follows; fallen snow (2.5-18μS/cm), snow drift under blizzard condition and deposited snow on sea ice (20-(10)^3μS/cm), part of them more than (10)^4μS/cm. From these measurments, it is pointed out that the electrocon-ductivity of deposited snow on sea ice depends on the presence of bare sea ice area. Under blizzard condition, it is suggested that snow drift originates from fallen snow and erosion of deposited snow on sea ice containing much sea salt, such snow drift is transported by strong wind. In this respect, if the sea salt can be evaporated, the appearance of sea salt particles is deduced. departmental bulletin paper